LAZOS FILIALES EN LA NARRATIVA DE NAJAT EL HACHMI - Zarco, Julieta (ConSecuencias, 2019)
Najat El Hachmi’s work is delineated by similar patterns of representation, such as the same nationality and ethnicity of its protagonists; the same concerns related to social and cultural heritage; with the arrival and adaptation to the receiving society; with the need to break the order imposed by patriarchy; with the conflict of having a border identity, as well as the construction of a feeling of a double belonging to two worlds, as to two cultures. All this is related to the weight of the legacy that links mothers and daughters. This article analyzes the construction of the subsidiary bonds of the protagonists of L’ultim patriarca and La filla estrangera from the representation of subalternity and emancipation, furthermore, coming from the sexual experiences of their protagonists. For this reason, the cultural studies of Gayatri Spivak (2002; 2006) in relation to the “silence to which the subaltern is subjected”, of Marianne Hirsh (1989), are taken into account to address the issues of “identification” and “disidentification” of daughters with mothers, and of Zygmunt Bauman (2003) regarding the issue of identity. All these questions will be translated into the narrators-protagonists as acts of rebellion, acts that the young women will use to find a new identity and, with it, the emancipation and freedom desired. Resumen La obra de Najat El Hachmi está delineada por patrones de representación similares, como la misma nacionalidad y origen étnico de sus protagonistas; las mismas inquietudes relacionadas con la herencia social y cultural; con la llegada y adaptación a la sociedad receptora; con la necesidad de romper con el orden impuesto por el patriarcado; con el conflicto de tener una identidad fronteriza, como también con la construcción de un sentimiento de doble pertenencia a dos mundos, es decir, a dos culturas. Todo ello se relaciona con el peso del legado que vincula a madres e hijas. El presente artículo analiza la construcción de los lazos filiales de las protagonistas de L’ultim patriarca y de La filla estrangera a partir de la representación de la subalternidad y de la emancipación, entre otras cosas, desde las experiencias sexuales de sus protagonistas. Para ello se toman en consideración los estudios culturales de Gayatri Spivak (2002; 2006) en relación al “silenciamento al que se ve sometida la subalterna”, de Marianne Hirsh (1989), para abordar las cuestiones de ‘identificación’ y ‘desidentificación’ de las hijas con las madres, y de Zygmunt Bauman (2003) con respecto al tema de la identidad. Todas estas cuestiones se traducirán en las narradoras-protagonistas como actos de rebeldía, actos de los que las jóvenes se valdrán para encontrar una nueva identidad y, con ello, la emancipación y la libertad anheladas.